Counselling Christian women on how to deal with domestic violence - Baker, Lynne M. (Bowen Hills, Qld. : Australian Academic Press, 2010)
"This book takes a very real look into the lives of Christian women who cope with domestic abuse on a daily basis. It explores their experiences of physical, verbal, emotional, sexual, financial, and spiritual abuse at the hands of their perpetrator husbands who claim themselves to be good Christian. Through extensive interviews combines with academic research, the reader comes face to face with the complexity of issues surrounding such domestic abuse and how counselling can be effective through the encouragement of a variety of religious and non-religious coping strategies. Of interest to victims of domestic abuse, as well as to the members of the clergy, psychologists, and counsellors, this book shows there is a place in the Christian church for women to separate and to be divorced without losing their faith." -- BOOK JACKET.
Includes bibliographical references pp. 241-271.
Issued also in printed form.
System requirements: Adobe acrobat reader to view PDF file.
Keywords: Abused wives -- Counseling of; Church work with abused women; Marital violence; Husband abuse; Wife abuse